2005
DOI: 10.1021/jm040137q
|View full text |Cite
|
Sign up to set email alerts
|

Design, Synthesis, and in Vitro Evaluation of Dipeptide-Based Antibody Minor Groove Binder Conjugates

Abstract: Antibody-drug conjugates (ADCs) were prepared consisting of DNA minor groove binder drugs (MGBs) attached to monoclonal antibodies (mAbs) through peptide linkers designed to release drugs inside the lysosomes of target cells. The site of linker attachment on the MGB was at the 5-position on the B-ring, since model studies showed that attachment of an electron-withdrawing group (i.e., acyl, carbamoyl) at this position increased the stability of the molecule. Because of the hydrophobic nature of the MGBs, severa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
56
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 82 publications
(57 citation statements)
references
References 40 publications
(103 reference statements)
1
56
0
Order By: Relevance
“…The duocarmycin class of compounds has been explored by several others for application in ADCs (38)(39)(40). The anti-CD70 ADC MDX-1203 is the only duocarmycin-based ADC; however, that has been taken into the clinic.…”
Section: Discussionmentioning
confidence: 99%
“…The duocarmycin class of compounds has been explored by several others for application in ADCs (38)(39)(40). The anti-CD70 ADC MDX-1203 is the only duocarmycin-based ADC; however, that has been taken into the clinic.…”
Section: Discussionmentioning
confidence: 99%
“…A comparison of IC 50 of free MMAF and c1F6-vcMMAF conjugate revealed that the molar concentrations of free MMAF required to elicit 50% killing in the RCC lines examined in this study was at least 10-fold higher than that delivered by 1F6-vcMMAF (Table 2), further illustrating the efficiency of drug delivery via CD70 targeting. Besides auristatinbased 1F6 conjugates, DNA-binding cytotoxic drugs have also shown potent, target-selective cytotoxic activities (46). This drug delivery capability is also not limited only to mAb 1F6.…”
Section: Discussionmentioning
confidence: 99%
“…Such linkers include hydrazone linkers, designed to hydrolyze upon internalization into acidic endosomes and lysosomes (1-3); peptide linkers optimized for cleavage by certain lysosomal proteases (3)(4)(5); and disulfide linkers, thought to be cleaved by the reducing environment within the endocytic pathway (6)(7)(8)(9)(10). In the latter category, the monoclonal antibody C242 against CanAg (a glycotope on the mucin1 (MUC1) colorectal tumor antigen) has shown efficacy against colorectal xenograft models in vivo when disulfide-linked to the ribosomal inhibitor ricin A chain via a 4-succinimdyloxycarbonyl-methyl-␣-[2-pyridyldithio]-toluene (SMPT) linker (11) and to the maytansinoid-derived microtubule active drug DM1 via an N-succinimidyl 4-(2-pyridyldithio)pentanoate (SPP) linker (12).…”
mentioning
confidence: 99%